2020
DOI: 10.1017/s0021932020000516
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of diabetes and TB among adults in India: a study based on National Family Health Survey data

Abstract: Multiple studies suggest that diabetes mellitus (DM) is a potential risk factor for tuberculosis (TB) development and treatment, especially in low- and middle-income countries. The study aimed to test concomitancy between DM and TB among adults in India. Data were from the 2015–16 National Family Health Survey (NFHS-4). The study sample comprised 107,575 men aged 15–54 and 677,292 women aged 15–49 for which data on DM status were available in the survey. The association between state-level prevalence of TB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…On the contrary, among those who self‐reported not having DM the figures were 407 men and 241 women (per 100 000). Furthermore, these authors found that adults from poor families, with low body mass index, low levels of literacy, and who were unemployed had a higher risk of TB‐DM comorbidity 31 . It is not clear if mycobacterium TB mutates to cause more MDR‐TB in patients with diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, among those who self‐reported not having DM the figures were 407 men and 241 women (per 100 000). Furthermore, these authors found that adults from poor families, with low body mass index, low levels of literacy, and who were unemployed had a higher risk of TB‐DM comorbidity 31 . It is not clear if mycobacterium TB mutates to cause more MDR‐TB in patients with diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these authors found that adults from poor families, with low body mass index, low levels of literacy, and who were unemployed had a higher risk of TB‐DM comorbidity. 31 It is not clear if mycobacterium TB mutates to cause more MDR‐TB in patients with diabetes. In a nested cohort ( n = 1633) studies of TB patients with and without DM in India, the authors found that phylogenetic reconstruction of all 76 paired Mtb strains showed genetically distinct isolates by participant origin, with 84% pairs acquiring at least one single‐nucleotide polymorphism (SNP) at treatment failure or recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Enabling factors for bi-directional screening include availability of facilities at the screening center, sensitized and trained staff, adequate financial resources for the health care facility for doing bi-directional screening and a robust NCD program. Review of studies shows that TB patients registered at tertiary and secondary health centers were more likely to be screened than primary health centers probably due to better availability of laboratories, testing facilities, positive attitude, better sensitization and awareness among treating physicians and healthcare workers [ 29 , 30 ]. Studies also show that the bi-directional screening is highly acceptable in the community if the health system can mobilize required additional resources [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…TB-Diabetes co-morbid cases have been rising in the past few years in India. 7,8,9 Diabetes is responsible for impaired immunity which often increases the likelihood of getting TB infection. TB on the other hand, adversely affects glucose tolerance, thus elevating the risk ofdiabetes.…”
Section: Introductionmentioning
confidence: 99%